Dinamika Pendistribusian Zakat Oleh Badan Amil Zakat Nasional (BAZNAS) di Provinsi Kalimantan Selatan - Magfirah, Rahmatul; Arbella, Kania; Rusdiyah, Rusdiyah (Sharia Journal and Education Center Publishing, 2026)
Zakat is a strategic instrument in Islamic philanthropy that functions spiritually and socio-economically to balance the economic system and alleviate poverty. The enormous potential of zakat in Indonesia requires professional management in accordance with Islamic law and Law Number 23 of 2011 concerning Zakat Management. BAZNAS South Kalimantan Province, as the official institution managing zakat, infaq, and sadaqah, plays an important role in the distribution of zakat. This study aims to examine the dynamics of zakat distribution by BAZNAS South Kalimantan Province from the perspectives of fiqh and zakat management. This research is an empirical legal study with a sociological and legal anthropological approach conducted at BAZNAS South Kalimantan Province and Baznas Microfinance Desa Kota Banjarmasin. Data was obtained through online interviews and literature studies, then analyzed qualitatively. The results of the study show that the distribution of zakat by BAZNAS South Kalimantan Province is dynamic. The distribution of consumptive zakat is focused on meeting the basic needs of mustahik through education, health, humanitarian, and da'wah and advocacy programs. Meanwhile, productive zakat is implemented through various utilization programs oriented towards the empowerment and independence of mustahik. From a fiqh zakat perspective, these distribution practices are basically in accordance with sharia provisions. However, zakat distribution still faces challenges in the form of low levels of awareness and compliance among some people in paying zakat through official institutions, uneven distribution of information to the public regarding zakat distribution through BAZNAS, and issues of sustainability of beneficiaries' businesses, as not all businesses run smoothly. Therefore, it is necessary to strengthen zakat management, improve zakat literacy, and strengthen business assistance with business experts so that zakat distribution can have an effective and sustainable impact.